TYPOLOGY OF MARKETING STRATEGIES FOR COMPANIES OF FOOD INDUSTRY - Joanna Szwacka-Mokrzycka (Polityki Europejskie, Finanse i Marketing)
The paper presents the typology of marketing strategies for food industry companies in Poland. The aim of this article is to determine the most effective strategies for food industry sector in Poland. The results of estimation of the selected food markets attractiveness (based on Porter’s 5 forces analysis) and segmentation (based on cyclical study TGI) are the base of typology of marketing strategies. Presented typology of marketing strategies based on research conducted in the period 1998-2012. In the framework of food industry there were selected the following branches for segmentation research: dairy, meat and edible fats. The results of research allowed to determination of possibilities of implementation of marketing strategies on the selected food markets. There are possibilities of wider use of strategies of market penetration and development and strategy of influencing on purchasers. The next recommended group are strategies of cooperation with partners in the field of distribution and strategy of the cost leadership, especially for large companies, which benefit from economies of scale. Next proposal is connected with differentiation strategy recommended for producers of new-generation products.